2015
DOI: 10.1007/s12630-015-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial anesthesia improves long-term survival after total joint replacement: a retrospective nationwide population-based study in Taiwan

Abstract: Introduction This study explored the effects of general (GA) and neuraxial (NA) anesthesia on the outcomes of primary total joint replacement (TJR) in terms of postoperative mortality, length of stay (LOS), and hospital treatment costs. Methods From 1997 to 2010, this nationwide population-based study retrospectively evaluated 7,977 patients in Taiwan who underwent primary total hip or knee replacement. We generated two propensity-scorematched subgroups, each containing an equal number of patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The use of regional anesthesia may influence the incidence and grade of BCIS, but this study is limited as all patients received general anesthesia, our standard for this operation in the cancer population. Studies in primary total hip arthroplasty found that neuraxial anesthesia is associated with shorter hospital stays, lower hospital costs, and improved long‐term overall survival compared with those in the general anesthesia group in mostly noncancer patient cohorts. The authors could not find a mechanism underlying the association between neuraxial anesthesia and long‐term survival .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of regional anesthesia may influence the incidence and grade of BCIS, but this study is limited as all patients received general anesthesia, our standard for this operation in the cancer population. Studies in primary total hip arthroplasty found that neuraxial anesthesia is associated with shorter hospital stays, lower hospital costs, and improved long‐term overall survival compared with those in the general anesthesia group in mostly noncancer patient cohorts. The authors could not find a mechanism underlying the association between neuraxial anesthesia and long‐term survival .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in primary total hip arthroplasty found that neuraxial anesthesia is associated with shorter hospital stays, lower hospital costs, and improved long‐term overall survival compared with those in the general anesthesia group in mostly noncancer patient cohorts. The authors could not find a mechanism underlying the association between neuraxial anesthesia and long‐term survival . However, the applicability of this to patients with cancer is controversial and no study has compared these anesthetic modalities in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies from countries including Taiwan, India, and the US have all consistently found that regional anesthesia-based approaches to operations as diverse as colorectal surgery, anterior cruciate ligament repair, total knee and hip arthroplasties, breast surgery, and carotid endarterectomy demonstrated faster recoveries, decreased side effects such as post-operative nausea, shorter hospital stays, and decreased overall costs when compared to general anesthesia and opioid-based approaches. 2329 Similarly, the public has great interest in containing the evolving disaster that is the US opioid epidemic. With approximately 10 million Americans reporting using opioids for non-medical reasons, nearly 2 million meeting substance abuse diagnostic criteria for opioids, and as many as 91 deaths every day due to opioid overdose, it is imperative that effective methods for opioid-sparing pain control be employed whenever possible.…”
Section: Stakeholdersmentioning
confidence: 99%
“…We were greatly interested in the recent article by Chen et al 1 assessing the effects of anesthesia methods on patient outcomes and long-term survival after total joint replacement (TJR). The authors showed that, compared with patients given general anesthesia, patients given neuraxial anesthesia had better long-term survival (58.2% vs 57.3%, respectively; P = 0.009), shorter length of hospital stay (8 [7-10] days vs 8 [6-10] days, respectively; P = 0.024) and lower hospital treatment costs ($4,079 [3,444] vs $4,113 [3,,568], respectively; P \ 0.001).…”
Section: To the Editormentioning
confidence: 99%